Parental Knowledge, Attitude and Practices Regarding Oral Health in Children Under 6 Years of Age - Kumar, S. Aravind (Journal of Neonatal Surgery, 2025)
Background: Early childhood caries is a prevalent chronic condition among young children, heavily influenced by parental knowledge, attitudes, and behaviors. Assessing these factors is vital for designing effective preventive strategies in primary dental care. Objectives: To evaluate parental knowledge, attitudes, and practices (KAP) related to oral health in children under 6 years of age and to analyze the interrelationships among these domains. Methods: A cross-sectional survey was conducted from May to July 2025 at a tertiary care hospital in India. One hundred and fifty parents of children aged 6 months to 6 years were enrolled consecutively from the pediatric outpatient department. A prevalidated 25-item questionnaire assessed knowledge (10 items; score 0–10, adequate ≥7), attitude (8 statements on a 5-point Likert scale; score 8–40, positive ≥32), and practices (7 questions on hygiene and dietary habits). Scores were summarized as mean ± SD or percentages. Pearson’s correlation tested associations between KAP domains. Statistical significance was set at p ≤ 0.05. Results: Participants had a mean age of 29.8 ± 5.4 years; 72% were mothers. The mean knowledge score was 7.1 ± 1.8, with 68% achieving adequate knowledge. The mean attitude score was 34.2 ± 3.6, and 74% exhibited a positive attitude toward preventive oral care. Practice assessment revealed that 81% assisted their child with toothbrushing twice daily, while only 28% had arranged a dental visit by age 2. The mean practice index was 5.2 ± 1.1. Knowledge correlated positively with practice (r = 0.35, p < 0.001) and attitude (r = 0.42, p < 0.001); attitude also correlated with practice (r = 0.29, p = 0.002). Conclusion:While most parents demonstrated moderate knowledge and positive attitudes toward their children’s oral health, gaps remain in early professional dental care and consistent hygiene practices. Targeted educational interventions are recommended to bridge these gaps and promote optimal oral health behaviors